The Effect of Plyometric Training Using Ankle Weights on Increasing Leg Muscle Power in Taekwondo - Mochammad Aziz Andrean Malik; Raden Boyke Mulyana; Yudi Nurcahya; Mulyana (Jurnal Pendidikan Jasmani (JPJ), 2026)
The purpose of this study is to determine the effect of plyometric training using ankle weights on increasing leg muscle power in the sport of taekwondo. The research method uses a quantitative experiment with a Pretest Posttest One Group Design research design. The population used is taekwondo athletes from the Club named Club Sukabumi Taekwondo Academy, totaling 46 Taekwondo Athletes, using a sampling technique that is simple purposive sampling to 12 taekwondo athletes who meet the criteria. The treatment given was 16 meetings at the beginning and end of the sample given a test in the form of Vertical Jumps Test. This research instrument uses the Vertical Jump Test to determine the level of ability in leg muscle power. After the data was obtained and analyzed using the SPSS Version 25 application, the data analysis technique used was the Paired Sample Test. The statistical results obtained from this study showed Sig. (2-tailed) of 0.000 smaller than the probability value of 0.05. Therefore, it can be decided that "H0 is Rejected". This means that there is a significant influence between plyometric training using ankle weights on increasing leg muscle power in the sport of taekwondo.